Correlation between Left Ventricular Eccentricity Index and Mean Pulmonary Arterial Pressure in Secundum Type Atrial Septal Defect Adult Patients - Citra Dewi Wahyu Fitria; Azhafid Nashar; Dyah Wulan Anggrahini; Anggoro Budi Hartopo; Hasanah Mumpuni; Lucia Kris Dinarti (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Background: Secundum type atrial septal defect (ASD) is the most common adult congenital heart disease. Hemodynamically, ASD result in a left-to-right shunt that causes right heart volume overload. This condition affects interventricular septal position and shape. Left ventricular (LV) eccentricity index (EI) suggests right ventricle (RV) overload when this ratio is >1.0. The aim of this study was to assess correlation between LV EI and mean pulmonary arterial pressure (mPAP) in secundum type ASD patients. Methods: We conducted a cross sectional study from ASD patients registry data. We enrolled subjects with secundum type ASD from the complete registry data. The LV EI was calculated from transthoracal echocardiography. The mPAP was measured by right heart catheterization as a gold standart. The correlation was performed by Spearman correlation test. Results: There were 40 adult secundum type ASD patients participated. The mean LV EI in enddiastolic was 1.55±0.39 and LV EI in end-systolic was 1.75±0.58. The median value of mPAP was 29 (12-99) mmHg. There was a moderate strength, positive and significant correlation between LV EI in end-diastolic and mPAP (r=0.37, p=0.018). The correlation was more significant and stronger between LV EI in end-systolic and mPAP (r=0.52, p=0.001). Conclusion: There was sufficiently strong and significant correlation between LV EI in both end-diastolic and end-systolic phase with mPAP in adult secundum type ASD.